2009
DOI: 10.3390/s90402746
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Effects in Ballistic High-Strained P-type Si Nanowire FETs

Abstract: In order to design and optimize high-sensitivity silicon nanowire-field-effect transistor (SiNW FET) pressure sensors, this paper investigates the effects of channel orientations and the uniaxial stress on the ballistic hole transport properties of a strongly quantized SiNW FET placed near the high stress regions of the pressure sensors. A discrete stress-dependent six-band k.p method is used for subband structure calculation, coupled to a two-dimensional Poisson solver for electrostatics. A semi-classical bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As one of the primary semiconductors, the relationship between the electrical properties of SiNWs and applied strain has attracted extensive attention. In the past decade, tremendous efforts have been dedicated to altering the straininduced carrier transport properties to develop highly sensitive strain gauges or a more effective mode for enhancing the carrier mobility based on theoretical calculations [17][18][19][20][21][22] or experiments [23][24][25][26][27][28][29][30]. It has been demonstrated that the orientation, size, doping type and level, as well as the strain state, are the primary factors [17,19,21,22] affecting the band structure, effective carrier mass, and electrical properties of strained crystalline Si.…”
mentioning
confidence: 99%
“…As one of the primary semiconductors, the relationship between the electrical properties of SiNWs and applied strain has attracted extensive attention. In the past decade, tremendous efforts have been dedicated to altering the straininduced carrier transport properties to develop highly sensitive strain gauges or a more effective mode for enhancing the carrier mobility based on theoretical calculations [17][18][19][20][21][22] or experiments [23][24][25][26][27][28][29][30]. It has been demonstrated that the orientation, size, doping type and level, as well as the strain state, are the primary factors [17,19,21,22] affecting the band structure, effective carrier mass, and electrical properties of strained crystalline Si.…”
mentioning
confidence: 99%
“…7,11 For Si, efforts have been paid to alter the carrier transport properties induced by strain in order to find highly sensitive strain gauges or a more effective mode to enhance the carrier mobility by theoretical calculations [21][22][23][24][25][26][27][28][29][30][31] or experiments. [32][33][34][35][36][37][38] It has been well demonstrated that the orientation, size, doping type, and level as well as the strain state are the primary factors 22,26,30,31 affecting the band structure, carrier effective mass, and electric properties for strained crystalline Si. In terms of directional considerations, the h100i, h110i, and h111i are the most important directions for the electrical transport properties of strained Si (particular one-dimensional Si) in practical applications or theoretical investigations.…”
mentioning
confidence: 99%
“…Since the carrier confinement in the 2D modeled QD is restricted to the xy-plane (see figure 1), the QD can be regarded as a nanowire in the evaluation of transition energy. The six-band k • p model for zincblende structures including the effects of strain is applied to calculate the band edge energies and effective masses which are modified by strain tensors, Luttinger parameters, and hydrostatic deformation potentials [37][38][39]. Numerical values of the relevant parameters can be found in the literature [39][40][41].…”
Section: Modeling and Simulationmentioning
confidence: 99%